Do face‐to‐face interactions support 6‐month‐olds' understanding of the communicative function of speech?. (21st September 2022) - Neff, Mary Beth; Martin, Alia
Abstract: Infants by 6 months recognize that speech communicates information between third parties. We investigated whether 6‐month‐olds always expect speech to communicate or whether they also consider social features of communication, like how interlocutors engage with one another. A small sample of infants watched an actor (the Speaker) choose one of two objects to play with (the target). When the Speaker could no longer reach her target object, she turned to a new actor (the Listener) and said a nonsense word. During speech, the actors were either face‐to‐face, the Speaker was facing away from the Listener, or the reverse. When the actors had been face‐to‐face, infants looked longer when the Listener selected the non‐target object compared to the target. Infants looked equally regardless of what the Listener chose when either actor had been disengaged. Area‐of‐interest gaze coding suggests that infants were similarly interested in the interaction across conditions, but their pattern of attention to Speaker and Listener differed when the Listener was disengaged during speech. Although these experiments should be replicated with a larger sample, the findings provide initial evidence that 6‐month‐olds do not expect speech alone to communicate, but also attend to the social context in which speech is produced.